Systematic Literature Review: The Effectiveness of Socio-Scientific Problem-Based Learning Models in Chemistry Learning - Husna, Asmaul; Yasmin, Nabila; Miterianifa (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study is a systematic literature review (SLR) that aims to analyze the effectiveness of the integrated Socio-Scientific Issues (PBL) Problem-Based Learning (PBL) model or PBL-SSI in improving students’ scientific abilities in chemistry learning in secondary school. The background of this research is the dominance of traditional lecture methods that fail to strengthen 21st century critical thinking and skills, demanding a change in a more contextual and participatory approach. The SLR procedure follows systematic, transparent, and replicable guidelines, with literature searches via Google Scholar (time range 2020–2025) using the keyword "SSI; PBL; Chemistry Learning". Based on strict inclusion criteria, as many as eight articles deserve comprehensive analysis. The results of the synthesis of findings show that PBL-SSI has proven to be significantly effective in strengthening students’ science literacy, critical thinking skills, creative thinking skills, and science process skills. The highest effectiveness is found in materials that have a strong relationship with social and environmental issues, such as acid-bases and green chemicals, which dominate the application of this model (about 25% each). The conclusion states that PBL-SSI is a very relevant approach to create meaningful and competency-oriented chemistry learning in the 21st century.